2001
DOI: 10.1598/rrq.36.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Phonemic Awareness Instruction Helps Children Learn to Read: Evidence From the National Reading Panel's Meta‐Analysis

Abstract: S A quantitative meta‐analysis evaluating the effects of phonemic awareness (PA) instruction on learning to read and spell was conducted by the National Reading Panel. There were 52 studies published in peer‐reviewed journals, and these contributed 96 cases comparing the outcomes of treatment and control groups. Analysis of effect sizes revealed that the impact of PA instruction on helping children acquire PA was large and statistically significant (d = 0.86). PA instruction exerted a moderate, statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
705
8
94

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,076 publications
(853 citation statements)
references
References 84 publications
46
705
8
94
Order By: Relevance
“…In several longitudinal studies, phonological awareness was found to be a powerful predictor of success in learning to read (Bowey, 2005; Ehri et al, 2001; Hulme, Bowyer‐Crane, Carroll, Duff, & Snowling, 2012). During the primary grades, the relation between phonological awareness and word reading efficiency in typically developing children appears stable and strong over time (e.g., Blachman, 2000; Hogan, Catts, & Little, 2005; Roman, Kirby, Parrila, Wade‐Woolley, & Deacon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In several longitudinal studies, phonological awareness was found to be a powerful predictor of success in learning to read (Bowey, 2005; Ehri et al, 2001; Hulme, Bowyer‐Crane, Carroll, Duff, & Snowling, 2012). During the primary grades, the relation between phonological awareness and word reading efficiency in typically developing children appears stable and strong over time (e.g., Blachman, 2000; Hogan, Catts, & Little, 2005; Roman, Kirby, Parrila, Wade‐Woolley, & Deacon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of phonics enables learners to use alphabetic code breaking skills to decode written words (Ehri & Nunes, 2002;Zimmerman et al, 2008). In learning to read words, students need to decode by transforming graphemes into a blend of phonemes (Ehri et al, 2001;Landerl, 2000;McGee & Ukrainetz, 2009;Scully & Roberts, 2002).…”
Section: Phonemic Awareness (Pa)mentioning
confidence: 99%
“…Par exemple, les enfants italiens réussissent mieux la segmentation de phonèmes que les enfants anglophones du même âge parce que la syllabe est plus ouverte et l'orthographe plus transparente en italien qu'en anglais. Enfi n, il est possible de développer ces capacités, au moyen d'entraînements adéquats qui évitent une approche skills and drills, de façon à faciliter l'apprentissage de la lecture (voir Ehri et al, 2001, pour une recension de 52 études, parmi lesquelles 41 concernaient l'anglais et 11 des langues autres que l'anglais, à l'exception du français).…”
Section: Les Capacités Métaphonologiquesunclassified